THE RELATIONSHIP OF SITTING POSITION WITH THE INCIDENT OF LOWER BACK PAIN EMPLOYEES OF THE LIBRARY AND ARCHIVES SERVICE RIAU PROVINCE IN 2020 - Retno Putri; Matdhika Sakti; Hafidh Triandha Khan; Bhukkar Adil Sjam (LPPM Universitas Abdurrab, 2023)
ABSTRACT Lower back pain (LBP) is one of the most common musculoskeletal health problems and is the largest contributor to global disability measured through years of living with disabilities (YLD), LBP is ranked sixth in from Disability Adjusted Life Years (DALYs). Low back pain is included in the top 10 diseases in Indonesia. Office employees often complain about NPB because of the work done in a long sitting position. The work process at the Department of Library and Archives of Riau Province, which requires a human role from a physical perspective, requires employees to work in positions for long periods of time which can cause ergonomic problems such as low back pain. The results obtained at the time of the study were 11 out of 15 employees complaining about NPB (73%). This research is to determine the correlation between sitting position and the LBP incident in the Riau Province Archives and Library employees in 2020. This research use an observational analytic method, with a cross-sectional study design. The sampling technique is simple random sampling with a sample size of 87 respondents. Data analysis uses the chisquare test. There is correlation between sitting position and NPB in Riau Province Library and Archives employees in 2020 with p-value = 0.034 (p-value <0.005).